Peran Brand Ambassador Dalam Membentuk Keputusan Pembelian Produk - Fisalsabila, Reva; Ramdhan, Arfian Suci; Yesya Vatria; Ayu Nurmala; Deswita; Pangastuti, Ariani Galuh (INTELEKTUAL ( E-Journal Administrasi Publik dan Ilmu Komunikasi ), 2025)
This study aims to investigate the function of brand ambassadors in influencing consumer purchasing choices through a case study of the selection of South Korean actor, Song Joong Ki, as the brand ambassador of the Scarlett Whitening product. Brand ambassador is a strategy in marketing communication aimed at strengthening brand image and establishing an emotional connection between consumers and products. In this study, the approach used is qualitative with a literature review method that studies various relevant academic sources in the last five years. The findings of this study indicate that the appointment of Song Joong Ki as a brand ambassador has a significant impact on increasing brand awareness, product credibility, and also driving consumer purchasing decisions. Visual appeal, good reputation, and high levels of trust in public figures such as Song Joong Ki are the main factors that strengthen the product image in the eyes of consumers. This approach has proven successful in reaching a wider audience, especially among young people who are influenced by the Korean Wave phenomenon. This study underlines that the use of famous international celebrities as brand ambassadors can increase the competitiveness of local brands amidst increasingly tight competition in the cosmetics industry.